(untitled) (KULT_online, 2015)
Nadine Muller and Joel Gwynne’s recent anthology Postfeminism and Contemporary Hollywood Cinema presents an insightful and multifaceted exploration of different key issues in critical postfeminist media studies. Divided into three parts, ’Postfeminist Femininities’, ’Postfeminist Masculinities’, and ’Postfeminism and Genre’, the fourteen contributions chart the modes of postfeminist subject formation through different genres of Hollywood cinema. Through constant recourse to canonical texts, key theorists, and seminal works the different essays demonstrate a well-informed understanding of the current debates and discussions. The collection becomes a particularly valuable scholarly work through its interlacing of theoretical accounts and close readings of concrete media texts.